Drug overdose deaths during prison riots and mental states of prisoners: a case study - Tomassini, Luca; Giuli, Gianni; Bottoni, Edoardo; David, Maria Chiara; Scendoni, Roberto (Frontiers in Psychiatry, 2024)
Prison riots, though often sensationalized in the media, have profound consequences, with a significant death toll. Prison populations, historically plagued by psychiatric disorders, witness high rates of suicide, particularly linked to turbulent events like riots. This study examines three drug overdose deaths resulting from a prison riot during the initial wave of the SARS-CoV-2 pandemic in Italy. To ascertain the nature of these deaths, a comprehensive toxicological analysis was conducted. Immunochemical screening and gas chromatography-mass spectrometry were employed to detect a spectrum of drugs, including MDMA, methadone, morphine, cannabis derivatives, benzodiazepines, and others. The toxicological findings revealed high concentrations of various substances in the biological fluids of the deceased inmates. Tramadol and mirtazapine were implicated in one case, while methadone was a common factor in the deaths of two inmates, one of whom also ingested diazepam. The synergistic effects of substances were explored, with methadone identified as a leading cause of death in two cases. Prison riots exacerbate drug abuse issues within prisons, leading to mass intoxication and overdose, as witnessed in historic incidents globally. The study underscores the challenges in determining whether such deaths are accidental, intentional (suicidal), or a consequence of uncontrollable drug consumption during a riot. The prison environment also amplifies pre-existing psychiatric disorders, and incidents like riots can trigger a cascade of uncontrollable psychological reactions. The three potential scenarios are drug dependence, accidental overdose in recreational drug use, and suicide attempts through substance ingestion.